Analisis Model Aplikatif Struktural Faktor Internal Terhadap Prestasi Akademik Mahasiswa FKIP Universitas Darussalam Ambon - Safarin Zurimi; Mursaid Dahlan (STMIK KHARISMA Makassar, 2016)
This study aims to verify a structural applicative models of student learning achievement FKIP Universitas Darussalam Ambon that can be expressed with regard to the influence of self-concept math, kecemasalan level of learning, emotional intelligence, Metacognition Awareness and motivation to learn. This study is an ex-post facto nature of causality and correlation. The population in this study were students FKIP Ambon University academic year 2016/2017. Data were collected through 214 sample chosen by proportional stratified random sampling technique. Data were analyzed with descriptive statistics and Structural Equation Model (SEM). Results showed that: (1) The concept of self positive and significant effect on learning achievement directly but indirectly through a significant learning motivation and metacognition awareness but not significant; (2) Anxiety learning and significant negative effect on learning achievement directly but indirectly through a significant learning motivation and awareness of metacognition; (3) Emotional Intelligence positive and significant effect on learning achievement, both directly and indirectly through learning motivation but insignificant through consciousness metacognition; (4) learning motivation positive and significant impact on student achievement FKIP Universitas Darussalam Ambon; (5) Awareness metacognition positive and significant impact on student achievement FKIP Universitas Darussalam Ambon